Interactional Dynamics During Residential Robbery: Victims’ Accounts and Reflections - Quinn, Caroline (University of the Witwatersrand, Johannesburg, 2021)
Several studies highlight the importance of documenting interactional elements of violent crime. While a range of studies focus on perpetrators’ accounts of what transpired during the commission of robberies and other forms of violent crime, there has been a notable oversight in establishing victims’ narratives surrounding such events. This study had a broad over- arching focus on establishing what appeared to either escalate or deescalate violence during a residential robbery from the survivors/victims’ perspective. In addition to this focus, it was further aimed to establish the cognitive appraisals that victims/ survivors reported as salient during the incident, as well as their reported motivations for behaviours they exhibited. Moreover, the study aimed to highlight any socio-demographic features that the victims perceived to be significant in their interaction with perpetrators. An exploratory approach to the research study was undertaken whereby semi-structured interviews were conducted with eight adult South African participants. The data was processed and presented by means of a thematic analysis and contextualized from a primarily realist paradigm. Five superordinate themes were identified across participants’ accounts, including: (1) Comprehending the Nature of the Interpersonal Interaction, (2) Negotiation of Dominance and Submission, (3) Cognitive Processing and Evaluation during the Event, (4) Awareness of Demographic and Socio-Cultural Aspects of the Interchange, and (5) Advice & Post Hoc Observations. These main themes were elaborated through subthemes that aimed to capture nuances across participants’ narratives. The findings suggested that although positioned in a subjugated role participants attempted to moderate or affect the interaction between themselves and the perpetrators. This was mainly achieved by verbally and behaviorally demonstrating compliance in order to mitigate further risk. In addition, participants described more complex ways of responding to perpetrators which appeared to be based on idiosyncratic evaluations of their particular situation. Participants were aware of limited agency but appear to have negotiated some means of retaining or displaying agency within situational constraints. Across all eight participants’ accounts, it was evident that participants acted in accordance with an assessment of their situation and responded in a manner that was perceived to result in ensuring the greatest likelihood of survival. References to race, gender, age and socioeconomic status did not feature as strongly in participants’ accounts as anticipated.
A research report Submitted in fulfillment of the requirements for a Master of Arts Degree MA by Coursework and Research Report in the field of Clinical Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2021
Keywords: Interpersonal violence; Interactions between victims and perpetrators; victims accounts of crime/ robbery; interactional dynamics during crime; cognitive appraisals during interpersonal crime; SDG-16: Peace, justice and strong institutions